A NOTE ON P-REGULAR SEMIRINGS - Dubey, M.K. (Italian Journal of Pure and Applied Mathematics, 2014)
The notion of P-regular semiring is introduced and characterization of the same has been given. We also study the representation of the elements in terms of quasi-ideals of weak P-regular semirings relative to the rightk-ideal P.